If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -2n = 3(-1n + 2) Reorder the terms: 2 + -2n = 3(2 + -1n) 2 + -2n = (2 * 3 + -1n * 3) 2 + -2n = (6 + -3n) Solving 2 + -2n = 6 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 2 + -2n + 3n = 6 + -3n + 3n Combine like terms: -2n + 3n = 1n 2 + 1n = 6 + -3n + 3n Combine like terms: -3n + 3n = 0 2 + 1n = 6 + 0 2 + 1n = 6 Add '-2' to each side of the equation. 2 + -2 + 1n = 6 + -2 Combine like terms: 2 + -2 = 0 0 + 1n = 6 + -2 1n = 6 + -2 Combine like terms: 6 + -2 = 4 1n = 4 Divide each side by '1'. n = 4 Simplifying n = 4
| 3m+8=3(4+m)-4 | | -48+(-13)= | | 6n+7-2n-14=4n+8 | | h(t)=-t-17 | | 3x^2-16x=64+y | | g(x)=5+0x | | 57+(-104)= | | x^2+x-48=3x | | 3n+6+n-8=2n-2+2n | | 3n+5(n-2)=3n+8(2-n) | | -43+81= | | 7(3-2n)-1=6-7n | | 52+(-7)= | | x^2-4x=-x+70 | | 5(3+x)-(8x+9)=-4 | | a(t)=12-4t | | -38+7= | | 10x+9=2x-7 | | 3x^4(1-x)=0 | | -3.2=-6.8 | | -16+-29= | | x^2+17=-10x+1 | | -2(4-3k)+8k= | | x^2-90=2x-10 | | -8(b-87)=-72 | | 4b+1-b=7 | | 5p+5-6=6p+3-30 | | -3x-8=-(2x+7) | | 3s+16=6+4s | | 3(5x+8)=-36 | | -40-5x+10x=45 | | x^2+18x+90=1 |